The Airbnb story : how three ordinary guys disrupted an industry, made billions... and created plenty of controversy - Gallagher, Leigh (Journalist) (Boston : Houghton Mifflin Harcourt, 2017)
A thorough and objective profile of this groundbreaking and unusual company covers its founders, meteoric rise, nagging troubles, and global popularity
Introduction -- The hustle -- Building a company -- Airbnb nation -- The bad and the ugly -- Air rage -- Hospitality, disrupted -- Learning to lead -- What's next?
Includes bibliographical references and index
Keywords: Airbnb (Firm); Hospitality industry; Bed and breakfast accommodations